CCNA 200-301 Volume 1: Official cert guide - Odom, Wendell (Official cert guide, 2024)
Trust the best-selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for exam success. They are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. CCNA 200-301 Official Cert Guide, Volume 1, Second Edition presents you with an organized test-preparation routine using proven series elements and techniques. Do I Know This Already? quizzes open each chapter and enable you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. CCNA 200-301 Official Cert Guide, Volume 1, Second Edition from Cisco Press enables you to succeed on the exam the first time and is the only self-study resource approved by Cisco. Best-selling author and expert instructor Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills.